Analyzing the concept of technical debt in the context of agile software development: A systematic literature review - Behutiye, Woubshet Nema; Rodríguez, Pilar; Oivo, Markku; Tosun, Ayse (Elsevier BV, 2017)
Technical debt (TD) is a metaphor that is used to communicate the consequences of poor software development practices to non-technical stakeholders. In recent years, it has gained significant attention in agile software development (ASD). The purpose of this study is to analyze and synthesize the state of the art of TD, and its causes, consequences, and management strategies in the context of ASD. Using a systematic literature review (SLR), 38 primary studies, out of 346 studies, were identified and analyzed. We found five research areas of interest related to the literature of TD in ASD. Among those areas, managing TD in ASD received the highest attention, followed by architecture in ASD and its relationship with TD. In addition, eight categories regarding the causes and five categories regarding the consequences of incurring TD in ASD were identified. Focus on quick delivery and architectural and design issues were the most popular causes of incurring TD in ASD. Reduced productivity, system degradation and increased maintenance cost were identified as significant consequences of incurring TD in ASD. Additionally, we found 12 strategies for managing TD in the context of ASD, out of which refactoring and enhancing the visibility of TD were the most significant. The results of this study provide a structured synthesis of TD and its management in the context of ASD as well as potential research areas for further investigation.
Keywords: Computer Science - Software Engineering